El género confesional como dimensión filosófica-literaria en María Zambrano y Rosa Chacel - Robles Luján, Cintia C. (2022)
In this work we intend to explore, from the works of María Zambrano and Rosa Chacel (both disciples of José Ortega y Gasset), the recovery of the confessional genre as a founding philosophical-literary dimension in their works. For this, we rely on a point of convergence in Zambrano and Chacel, where the Confession is presented as the horizon of revelation from a narrative of the self, for the recognition of biographical-self-referential elements. We try to show that the confessional genre, although it is a substantive part of the anthropological-literary treatment that both authors carry out, also leads to being a renewal proposal for contemporary man.